Basal exon skipping and nonsense-associated altered splicing allows bypassing complete CEP290 loss-of-function in individuals with unusually mild retinal disease. (16th May 2018) - Barny, Iris; Perrault, Isabelle; Michel, Christel; Soussan, Mickael; Goudin, Nicolas; Rio, Marlène; Thomas, Sophie; Attié-Bitach, Tania; Hamel, Christian; Dollfus, Hélène; Kaplan, Josseline; Rozet, Jean-Michel; et al.
Abstract: CEP290 mutations cause a spectrum of ciliopathies from Leber congenital amaurosis type 10 (LCA10) to embryo-lethal Meckel syndrome (MKS). Using panel-based molecular diagnosis testing for inherited retinal diseases, we identified two individuals with some preserved vision despite biallelism for presumably truncating CEP290 mutations. The first one carried a homozygous 1 base pair deletion in Exon 17, introducing a premature termination codon (PTC) in Exon 18 (c.1666del; p.Ile556Phefs*17). mRNA analysis revealed a basal exon skipping (BES) of Exon 18, providing mutant cells with the ability to escape protein truncation, while disrupting the reading frame in controls. The second individual harbored compound heterozygous nonsense mutations in Exon 8 (c.508A>T, p.Lys170*) and Exon 32 (c.4090G>T, p.Glu1364*), respectively. Some CEP290 lacking Exon 8 were detected in mutant fibroblasts but not in controls whereas some skipping of Exon 32 occurred in both lines, but with higher amplitude in the mutant. Considering that the deletion of either exon maintains the reading frame in either line, skipping in mutant cells likely involves nonsense-associated altered splicing alone (Exon 8), or with BES (Exon 32). Skipping of PTC-containing exons in mutant cells allowed production of CEP290 isoforms with preserved ability to assemble into a high molecular weight complex and to interact efficiently with proteins important for cilia formation and intraflagellar trafficking. In contrast, studying LCA10 and MKS fibroblasts we show moderate to severe cilia alterations, providing support for a correlation between disease severity and the ability of cells to express shortened, yet functional, CEP290 isoforms.